(untitled) (London Journal of Medical and Health Research, 2025)
Antibiotic stewardship is at the center of the healthcare system of the future, in a world where antimicrobial resistance (AMR) is a rapidly growing threat. The primary causes of resistance have been the abuse and overuse of antibiotics in clinical, community, and agricultural settings. As a result, patient outcomes have been negatively impacted, leading to longer illness durations, higher death rates, and higher healthcare expenses. Antibiotic stewardship programs (ASPs) employ evidence-based guidelines, diagnostics, surveillance, and interdisciplinary collaboration to prevent needless antibiotic use. Antibiotic use during direct patient care, surveillance, infection prevention, and health education can be greatly influenced by nurses, who make up the majority of the healthcare workforce It also discusses how to strengthen nursing leadership and stewardship capacity in the future.